New Zealand Paramedic-Based Systems of Care for ST-Elevation Myocardial Infarction Patients: Autonomous Delivery of Fibrinolytic Treatment and Cardiac Catheterisation Laboratory Referral - Davis, Paul (Auckland University of Technology, 2018)
The pathology of ST-elevation myocardial infarction (STEMI) represents a serious and potentially life-threatening medical emergency that affects thousands of unsuspecting New Zealanders each year. To optimise patient outcomes, efficient and contemporary systems of care are required with a primary goal of achieving timely diagnosis and access to definitive reperfusion therapy. Internationally, paramedics have played a crucial role in helping meet this objective through a variety of processes and given their strategic position within the community. They are often the first health practitioners to attend STEMI patients, and thus are well-positioned to expedite the process of diagnosis, treatment, management and referral. However, within this capacity, the New Zealand paramedic workforce has been under-utilised. Although some regions have adopted ambulance-based programmes for pre-hospital fibrinolysis and early hospital notification, the antiquated physician-assisted telemetry-based models employed are often costly, time-consuming and prone to technological failings. This doctoral thesis details three investigations undertaken with the St John Ambulance Service, the country’s main emergency ambulance provider. It includes a preliminary simulation-based study followed by two multi-regional clinical trials, with an overarching focus on a new autonomous paramedic-based STEMI management system. The efficiency, safety and feasibility of an independent paramedic decision making model for the provision of out-of-hospital fibrinolysis and cardiac catheterisation laboratory (CCL) activation is examined in a real-world setting. Comparisons are then made to that of previous processes requiring physician-oversight and authorisation. Internationally, this research is the first to undertake such an analysis. The results of this research have shown significant improvements among all treatment timeline metrics for both fibrinolysis and primary percutaneous coronary intervention (PPCI) in favour of an autonomous paramedic model. In some cases, this expedited care has subsequently yielded both morbidity and mortality benefit and in all cases, a reduced hospital length of stay. Moreover, our New Zealand paramedics have demonstrated highly accurate clinical decision making abilities, reflective of recent professional advancements in both education and training. These findings have served to address several failings within our current healthcare system towards the treatment and management of STEMI patients, while making a significant contribution to the knowledge and understanding of paramedicine, both nationally and abroad. This research has the capacity to inform multidisciplinary policies and bring about meaningful clinical practice change in New Zealand.
Keywords: Paramedic; STEMI; Fibrinolysis; Percutaneous coronary intervention; Helivac; MI